Population history of Brazilian south and southeast shellmound builders inferred through dental morphology. Issue 2 (11th June 2021) - Fidalgo, Daniel; Hubbe, Mark; Wesolowski, Veronica
Abstract: Objective: The Southeast and South Coast of Brazil was inhabited during most of the Holocene by shellmound builders. Although there are cultural differences in the archaeological record between regions, it is still debatable how these differences may relate to different population histories. Here, we contribute to this discussion by exploring dental morphological affinities between several regional series. Materials and Methods: Dental morphology of 385 individuals from 14 archaeological sites was analyzed using the Arizona State University Dental Anthropology System. Fifteen traits were used to explore morphological affinities among series through Euclidean distance, Mean Measure of Divergence, and Principal Component Analysis. Mantel matrix correlation and partial correlation tests were used to examine the association between biological, geographic, and chronological distances. Results: Morphological affinities show that ceramic and nonceramic South Coast groups cluster and differ from most Southeast series. In contrast, Southeast coastal and riverine groups display high morphological variance, showing less biological coherence among them. These biological distances between regions are partially explained by geography, but not by chronology. Conclusions: The results support that these coastal populations were low‐mobility groups. Although interactions between individuals of different regions likely existed, gene flow occurred mostly among individuals from local or adjacent areas. The introduction of ceramic in the South Coast is not associated with changes in dental morphology patterns, suggesting its adoption is not exclusively associated with the arrival of different biological groups. Southeast coastal and riverine groups show high phenotypic diversity, suggesting a different history of human occupation and cultural development than observed in the South Coast. Research Highlights: There is high phenotypic variance among Brazilian precolonial coastal societies. Gene flow is partially mediated by geography, but not chronology, suggesting local continuities over time. In the South region, the arrival of ceramic is not associated with biological differences in dental traits. The cultural differences between South and Southeast Coast are associated with biological differences between them.